2007
DOI: 10.1063/1.2730572
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric and magnetic properties of CdMnS films prepared by coevaporation

Abstract: We report on impurity ferroelectricity and ferromagnetic properties in semiconductor-structured CdMnS films. We observed ferroelectric hysteresis in CdMnS. A remnant polarization of 1.72 μC/cm2 and a coercive field of 14.3 kV/cm were obtained in samples with Mn concentration below 2%. The coevaporated CdMnS samples become ferromagnetic when doped with Au, with a spontaneous magnetization of 1.39×10−6 emu and a coercive magnetic field of 75.4 gauss at 10 K, and the Curie point was found to be higher than room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…As the Cd concentration is increased, the diffraction peaks become broader due to a reduction in the grain size [11]. Similar results are reported for Mn-doped CdS films [11,12]. The value of D calculated for PbCdS films was found to be in the range of 9-11 nm.…”
Section: Methodssupporting
confidence: 83%
“…As the Cd concentration is increased, the diffraction peaks become broader due to a reduction in the grain size [11]. Similar results are reported for Mn-doped CdS films [11,12]. The value of D calculated for PbCdS films was found to be in the range of 9-11 nm.…”
Section: Methodssupporting
confidence: 83%
“…Only a few show ferromagnetism at room temperature . On the other hand, many examples of the Mn/CdS are known to exhibit ferromagnetic properties around cryogenic temperatures. , More often, manganese-doped CdS and CdSe have been reported to exhibit superparamagnetism or antiferromagnetism coupled superparamagnetism at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the increase in both deposition time and temperature yield as slight decrease in band gap from 3.88 eV to 3.81 eV. This could be attributed to the quantum size effects [7,8]. (b)deposition time.…”
Section: Resultsmentioning
confidence: 98%